On farm grass-legume pasture performance in the Peruvian rainforest - Reategui del Aguila, K; Vera, Raúl R.; Loker, WM; Vásquez, M. (Cambridge University Press, 1995)
The possible use of tropical forage legumes in pastures based on Brachiaria decumbens and Andropogon gayanus pastures was tested on farms in the humid tropics region of Pucallpa, Perú. The pastures were established by farmers using manual labour. They were associated with maize in some cases and were normally grown without fertilizers. The pastures were established in areas where fallow regrowth was felled and burnt. These pastures, with grass-alone controls, were incorporated by farmers into their normal paddock rotation and were grazed by dual-purpose cows. Despite the variable terrain and soil conditions, all the pastures established and persisted well. Over a four year period under grazing, the legume contribution to the forage averaged 21% and ranged between 1 and 66%. Desmodium ovalifolium was the dominant legume in paddocks that were not burnt, whereas in pastures regularly burnt to control weeds it tended to disappear and Stylosanthes guianensis was the main legume present. It is concluded that where farmers ensure the maintenance of adequate levels of forage, grass-legume mixtures are a viable and persistent option even if the pasture is occasionally burnt.